UPAYA ORANG TUA SISWA DALAM MENINGKATKAN DISIPLIN SISWA TERHADAP PERATURAN DI MADRASAH TSANAWIYAH NEGERI BANJARMASIN SELATAN 1 BANJARMASIN - Zainal Fauzi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2014)
Purpose of this study was to determine the extent to which the activity of parents in attempt to provide guidance to help students to learn responsible as a student at the school and to find out about the monitoring / supervision of student learning activities, both at home, at school, and in society. The study population was all students and student MTs Negeri Banjarmasin Banjarmasin South 1, amounting to 148 people, which consists of 6 classes: VII D, VII E, VIIIA, VIIIB, IXA, IXB. The efforts of parents in improving student discipline against such regulation is expected to increase discipline in bersosialisasikan children learn and be able to follow the learning process with a sense of security, calm, comfortable, so the learning process and result can run well and smoothly. Keywords: Effort, parents, students Discipline Regulation.